Respiratory viral infection and wheezy bronchitis in childhood. Issue 1 (February 1979) - Horn, M E; Brain, E A; Gregg, I; Inglis, J M; Yealland, S J; Taylor, P
Abstract : The role of respiratory viral infection in wheezy bronchitis was studied in 163 children, aged 0-12 years, in a London general practice. Virological investigations were also performed when these same children had acute upper respiratory illness without wheeze. A virus was isolated in 146 (26.4%) of 554 episodes of wheezy bronchitis, rhinoviruses accounting for almost half of the isolations. The relative frequency with which individual viruses were isolated in wheezy bronchitis was similar to that in acute upper respiratory illness in 180 other children who had never had wheezy bronchitis. The large number of isolations of rhinoviruses in wheezy bronchitis is probably due to their numerous serotypes and the absence of cross-immunity between them. Our findings have confirmed that infection by respiratory viruses can provoke wheezy bronchitis in certain children, in whom host factors are an important predeterminant. In children with a previous history of wheezy bronchitis infection by rhinoviruses was associated significantly more often with such an episode than with upper respiratory illness. The maturation of protective mechanisms, including the acquisition of specific immunity to a progressively larger number of viruses, could explain the fall in the age-incidence of wheezy bronchitis.